2005
DOI: 10.1097/01.scs.0000179744.91165.3a
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Ultra-Thin Porous Polyethylene Implants used for Reconstruction of Orbital Floor Defects

Abstract: We recommend the use of ultra-thin porous polyethylene implants in the reconstruction of the orbital floor defects in facial trauma patients. The implants are durable in the long-term and mimic the anatomy of the thin orbital floor and avoid the morbidity of autogenous bone grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 21 publications
2
31
0
2
Order By: Relevance
“…Correction of enophthalmos has showed better results with Medpor as seen in studies by Lee et al [21], Otzturk et al [22] and Lin et al [23] as 4.1, 7.9 and 14.3 %, respectively.…”
Section: Enophthalmosmentioning
confidence: 86%
See 1 more Smart Citation
“…Correction of enophthalmos has showed better results with Medpor as seen in studies by Lee et al [21], Otzturk et al [22] and Lin et al [23] as 4.1, 7.9 and 14.3 %, respectively.…”
Section: Enophthalmosmentioning
confidence: 86%
“…Medpor was used by studies by Lee et al [21], Otzturk et al [22] and Lin et al [23] for orbital fractures and have reported rate of diplopia to be 3.5, 2.6 and 4.5 %, respectively.…”
Section: Diplopiamentioning
confidence: 99%
“…), [26][27][28][29][30][31] allogenic grafts, [32,33] and alloplastic materials (silicone, polytetrafluoroethylene, hydroxylapatite, porous polyethylene, titanium, and Vitallium mesh). [34][35][36][37][38][39][40][41] There are studies outlining their advantages, disadvantages and success rates. Cadaver-based allogenic bone grafts are not preferred due to risk of viral infection transmission, resorption rate and their costly nature.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies showing the superiority of porous polyethylene over other graft materials. [34,35,41] Ng et al [13] performed a study on 30 orbital floor fracture cases treated by porous polyethylene, and none of the patients exhibited a need for removal of the implant within a follow-up period of 9 months. They described the porous polyethylene layer as a strong and easily malleable material preventing donor-site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Uma desvantagem é não permitir controle radiológico, por ser radiolúcido. Poucas complicações têm sido relatadas com seu uso 22,23 . Este material foi aprimorado, melhorando suas caracterís-ticas mecânicas e tornando-se radiopaco, com a incorporação, ao seu interior, de uma tela de titânio (Medpor Titan ® , Porex Corporation, USA) (Figura 8).…”
Section: Polietileno Poroso De Alta Densidadeunclassified